The Couple Satisfaction Questionnaire: Development and Validation with Two Italian Samples - Antonelli, Elena; Ronconi, Lucia (Advances in Social Sciences Research Journal, 2022)
This paper reports on the development and validation of a questionnaire to measure couple satisfaction in the Italian population, the Couple Satisfaction Questionnaire (CSQ). The CSQ is focused to assess global couple satisfaction, that is the subjective evaluation of one’s couple relationship as a whole. Results: The exploratory factor analysis (EFA) in the pilot study indicated the existence of two dimensions, one positive and one negative with respect to couple satisfaction. This separation has been interpreted as a methodological artifact due to item phrasing. In fact, the confirmatory factor analysis (CFA) in the validation study supported our hypothesis of one latent factor. The CSQ showed to have good psychometric properties, including high internal consistency, and excellent convergent validity. Discriminant validity referring to social desirability was acceptable. Conclusion: The pilot and validation studies’ results suggest that the CSQ is a reliable instrument to assess couple satisfaction in couple or family counselling, and encourage further studies of its psychometric properties.